Migrant Parents and the Psychological Well-Being of Left-Behind Children in Southeast Asia - Graham, Elspeth (Blackwell Publishing Ltd, 2011)
Several million children currently live in transnational families, yet little is known about impacts on their health. We investigated the psychological well-being of left-behind children in four Southeast Asian countries. Data were drawn from the CHAMPSEA study. Caregiver reports from the Strengths and Difficulties Questionnaire (SDQ) were used to examine differences among children under age 12 by the migration status of their household (N = 3,876). We found no general pattern across the four study countries: Indonesia, the Philippines, Thailand, and Vietnam. Multivariate models showed that children of migrant fathers in Indonesia and Thailand are more likely to have poor psychological well-being, compared to children in nonmigrant households. This finding was not replicated for the Philippines or Vietnam. The paper concludes by arguing for more contextualized understandings.